DEPRESSIVE SYMPTOMS IN CAREGIVERS OF OLDER MEXICAN AMERICANS: A FOLLOW-UP STUDY OF THE HEPESE WAVE 7 AND 9. (11th November 2018) - Flores, D; Rote, S; Angel, J; Chen, N; Downer, B; Markides, K
Abstract: Objective: Examine the degree of care recipients' degenerative functional disability, cognitive impairment, and other factors associated with increased depressive symptoms among caregivers and their influence on the caregiving dynamic. Methods: This study accessed data from Wave 7 (2010–11) and Wave 9 (2016) of the Hispanic Established Populations for the Epidemiologic Study of the Elderly. Final follow-up sample included 206 adult caregivers that provided personal, medical, and household care assistance to older parents. Care recipients' functional ability on activities of daily living (ADLs), cognition, neuropsychiatric symptoms (NPI), caregiver perceived social stress, and caregiver depressive symptoms were assessed. A multivariable logistic regression analysis was conducted to assess the effect of change of neuropsychiatric disturbance on the increased development of caregiver depressive symptoms. Results: Results find increased care recipient NPI symptoms was significantly associated with the increased caregiver depressive symptoms. Also, greater odds of inability to cope and increased stress on caregivers related to caregiver depressive symptoms. Conclusions: In Mexican American families' disability, diminished cognition, caregiver stress, and dementia related neuropsychiatric symptoms take an increased toll on caregivers. The need to provide respite, mental health and community services for caregivers is of paramount importance to alleviate depressive symptoms and burden.